2023
DOI: 10.3390/su15065402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Effective Production of Biocement for Soil Solidification and Wind Erosion Control

Abstract: Biocement can be achieved through the microbially induced carbonate precipitation (MICP) process. Such a method can potentially be utilized as an eco-friendly method for civil and environmental engineering applications such as soil ground improvement and wind erosion control of surface soil. In this method, one key step is the effective production of ureolytic bacteria. In previous laboratory and field studies, the cultivation and production of the bacteria used for the MICP were usually expensive and time-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, when error bars are taken into consideration, there appears to be minimal difference between the two sets of results shown. Similarly, Hang et al [43], reported that the use of urea as the nitrogen source for MICP, when conducting aqueous studies over 24 h, led to an increase in pH and that this increase wasn't not observed when supplying ammonium chloride (NH4Cl) only as the only nitrogen source. The results for the mass of precipitate (assumed at this stage to be calcium carbonate) deposited within the centrifuge tubes after 24 h, are presented in Figure 4.…”
Section: Batch Test Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, when error bars are taken into consideration, there appears to be minimal difference between the two sets of results shown. Similarly, Hang et al [43], reported that the use of urea as the nitrogen source for MICP, when conducting aqueous studies over 24 h, led to an increase in pH and that this increase wasn't not observed when supplying ammonium chloride (NH4Cl) only as the only nitrogen source. The results for the mass of precipitate (assumed at this stage to be calcium carbonate) deposited within the centrifuge tubes after 24 h, are presented in Figure 4.…”
Section: Batch Test Resultsmentioning
confidence: 99%
“…Results indicate that it may be possible to include less ammonium chloride in the medium than used in this study. While the nitrogen source provided for ureolytic MICP studies is typically urea, ammonium chloride can also be a source of nitrogen [43]. Hang et al [43] reported that the optimum nitrogen source for MICP, when compared to ammonium chloride, was urea.…”
Section: Efficiency Of Chemical Conversionmentioning
confidence: 99%
See 3 more Smart Citations